TEACHER TRAINING AND INCLUSIVE TEACHING PRACTICES IN SERVING STUDENTS WITH ATTENTION DEFICIT HYPERACTIVITY DISORDER IN THE EARLY YEARS OF ELEMENTARY SCHOOL (REMUNOM, 2025)
Attention deficit hyperactivity disorder (ADHD) is one of the main contemporary challenges to inclusive education, especially in the early years of elementary school, requiring teachers to have specific training, differentiated teaching practices, and ongoing institutional support. This study aims to analyze the pedagogical practices used by teachers in serving students with ADHD in the public school system, as well as to discuss the role of initial and continuing training in the implementation of inclusive processes. This is a qualitative, exploratory study developed through a systematic literature review based on scientific publications from 2020 to 2025, selected on Google Scholar using the keywords “ADHD” and “learning”. The analysis of the studies showed that, although there have been regulatory advances in the field of inclusion, significant weaknesses persist in teacher training, in the use of adapted pedagogical strategies, and in the multidisciplinary support offered by educational institutions. The results indicate that the lack of specific knowledge about the disorder and the precariousness of continuing education directly impact the quality of educational services for students with ADHD. It can be concluded that strengthening teacher training, combined with consistent public policies and interdisciplinary work between schools, families, and health professionals, is an indispensable condition for promoting truly inclusive education.